Inhibition of ARH2 by pH/ROS-responsive nanosystem for improved lung adenocarcinoma immunochemotherapy - Rui Cai; Meng Wang; Mengting Pan; Zhiwu Zhang; Qiang Jia; Longbao Feng; Zhongjian Yu; Lu Liu; Tongyu Zhu; Silin Cai; Han Tian; Jiangyu Zhang; et al. (Bioactive Materials)
Immunotherapy resistance remains a substantial barrier to improving treatment outcomes for patients with lung adenocarcinoma (LUAD). Identifying effective immunotherapy target is crucial for enhancing therapeutic efficacy in LUAD. Through database analysis, we discovered that ADP ribosylhydrolase-like 1 (ADPRHL1, ARH2) is associated with immunosuppression. In this study, we first demonstrated that the increased presence of ARH2-positive macrophages in LUAD tumors is associated with immunosuppression. Furthermore, ARH2 promotes M2 macrophage polarization and suppresses immune responses by regulating the FPR2/PI3K/AKT signaling pathway. Additionally, we found that artesunate (ART) can induce necroptosis in LUAD cells and activate antitumor immune responses. To translate these findings into a clinically viable therapeutic approach, we developed a pH/ROS-responsive nanosystem capable of co-delivering siARH2 and ART. This nanosystem effectively activated immune responses in both tumor cells and tumor-associated macrophages. Furthermore, the nanosystem demonstrated excellent in vivo safety, precise PD-L1 targeting, and responsiveness to ROS and pH variations. It considerably suppressed the malignant phenotype of tumor cells induced by macrophages and enhanced T-cell-mediated immune responses. Overall, targeting ARH2 in combination with ART represents a promising novel strategy for the treatment of LUAD.